Relasi Politik dan Isu Agama: Dinamika Politik PKS dan Aksi Bela Islam pada Pemilu Serentak 2019 - Nabil Lintang Pamungkas; Agung Widiyantoro; Moddie Alvianto Wicaksono (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2020)
This paper believes the tendency to use religious issues as a political instrument in the momentum of elections in Indonesia. Some research said the issue of religion is a supporting factor for polarization in society and influences the subjectivity of voters in determining the representation of their aspirations. The author is interested in the consistency of the Prosperous Justice Party (PKS) political support for the Aksi Bela Islam (Islamic Defending Action) which emerged as a movement that raised the issue of blasphemy and the criminalization of Ulama. This study aims to analyzing the potential of PKS using religious issues as political instruments to obtain and strengthen support in elections. This research uses a library method in which there are several literatures and scientific sources that are relevant to the focus of the case. Political relations formed through religious issues between PKS and Aksi Bela Islam from 2016 to the 2019 Election were so dynamic. The results of the study interpret the PKS's political attitude against Aksi Bela Islam as (1) political support that reflects the practice of Indonesian democracy, (2) PKS calls on Muslims to actively participate in every agenda of the Aksi Bela Islam, by obeying and following the fatwas of Islamic leaders who delivered in the forum, and (3) PKS calls for not choosing leaders who have criminalized Ulama. Thus, studies show that PKS has an electoral interest behind political relations with Aksi Bela Islam by utilizing religious issues.